2011
DOI: 10.1177/1359104511399843
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent boys with sickle cell disease: A qualitative study

Abstract: Sickle cell disease is a recessively inherited blood disorder associated primarily with black communities within the UK. This study investigated the experiences of adolescent boys with this condition. Eight participants were interviewed and their responses analysed using Interpretative Phenomenological Analysis. The emergent themes were watchfulness, holding onto normality, and connecting and disengaging. This analysis illustrated connections between physical symptoms, emotional responses and the development c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(38 citation statements)
references
References 30 publications
1
35
2
Order By: Relevance
“…This finding is consistent with two earlier published qualitative studies in the United Kingdom (Erskine, 2012;Fuggle, Shand, Gill, & Davies, 1996). Fuggle and colleagues (1996) noted that adolescents tended to underreport their pain levels and dismiss the negative effects of SCD on their daily lives, which could be a coping mechanism in order to avoid blood tests and possible hospitalizations, whereas Erskine (2012) found that some boys claimed to miss medical appointments and not to take their recommended daily medication, which he surmised to be a wish to maintain an ordinary teenage life. We likewise conjecture that this dismissal and denial of the negative effects of their disease reflects a palpable yearning for normalcy among participants, or at least the need to create a normal image of themselves in front of others.…”
Section: Discussionsupporting
confidence: 95%
See 2 more Smart Citations
“…This finding is consistent with two earlier published qualitative studies in the United Kingdom (Erskine, 2012;Fuggle, Shand, Gill, & Davies, 1996). Fuggle and colleagues (1996) noted that adolescents tended to underreport their pain levels and dismiss the negative effects of SCD on their daily lives, which could be a coping mechanism in order to avoid blood tests and possible hospitalizations, whereas Erskine (2012) found that some boys claimed to miss medical appointments and not to take their recommended daily medication, which he surmised to be a wish to maintain an ordinary teenage life. We likewise conjecture that this dismissal and denial of the negative effects of their disease reflects a palpable yearning for normalcy among participants, or at least the need to create a normal image of themselves in front of others.…”
Section: Discussionsupporting
confidence: 95%
“…However, unlike in previous studies, none of the participants mentioned that he or she was bullied or marginalized (Erskine, 2012). Although this lack of bullying and marginalization may be a true reflection of what is happening in their lives, it may also be that participants are reluctant to disclose any bullying in order to feel accepted by peers.…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…Stegenga & Burks (2013) & Valenzuela et al (2013 used photovoice which "is often valued for its ability to uncover rich descriptive information" (Catalani & Minkler, 2010;pp.441). Erskine (2011) used Interpretative phenomenological analysis (IPA) which uses a psychological focus to help explore participant's experiences, understandings, perceptions and views (Brocki & Wearden, 2006). Atkin & Ahmad (2001) and Thomas & Taylor (2002) were the only studies conducted over a longer period of time.…”
Section: Methodmentioning
confidence: 99%
“…All the studies, bar Erskine (2011), gave perspectives from both genders increasing the credibility. Erskine (2011) recruited male adolescents only. Polit & Beck (2013) found that gender bias was generally observed when females alone were sampled and in the Erskine (2011) study it was good to have the male perspective as it can be challenging to recruit males to such studies.…”
Section: Sample Size and Gendermentioning
confidence: 99%